Broadband stepped-frequency modulated continuous terahertz wave tomography for non-destructive inspection of polymer materials. (July 2019) - Zhang, Xiaoxuan; Guo, Qijia; Chang, Tianying; Cui, Hong-Liang
Abstract: An all-solid-state electronic three-dimensional terahertz tomography system designed specifically for non-destructive inspection of polymer materials is demonstrated, which is capable of determining the positions and shapes of hidden defects accurately. The imaging radar system, based on stepped-frequency modulated continuous wave (SFMCW), with center frequency at 180 GHz, bandwidth of 60 GHz, and average power 0.5 mW, is tested against thick Teflon (polytetrafluoroethylene, PTFE) plates with internal voids as samples. The locations and shapes of the hidden holes are obtained in both electromagnetic simulation and experimental measurements with a three-dimensional image reconstruction algorithm, which features advantages of accurate reconstructed image details and fast computation speed, demonstrating that the terahertz imaging radar system combined with the algorithm developed is capable of detecting internal defects of thick polymers. Key resolution parameters are established experimentally in detail, demonstrating 2.5 mm and 1.7 mm range resolutions in free space and in Teflon separately, and lateral spot diameters ranging from 3.4 mm to 8 mm at imaging distances from 5 mm to 60 mm. Highlights: An all-solid-state electronic 3D terahertz tomography system designed for NDI of polymer materials is demonstrated. Hidden defects are obtained by a 3D image reconstruction algorithm, which features accuracy and fast computation speed. A judgment basis for quantitative measurements of defect's cross-range size is summarized, which is suitable for other polymers. Key resolution parameters and appropriate detection distance are established experimentally and discussed in detail. The new approach is far-reaching significance for non-destructive inspection of polymer materials.